Strengthening Legal Aspects in Order to Mitigare Legal Risk of Mudharabah Muqayyadah on Balance Sheet Transaction in PT Bank XYZ - Sulaeman, Eman Achmad; Wiryono, Sudarso Kaderi (The Indonesian Journal of Business Administration, 2013)
The growth of Sharia Bank in Indonesia has increased significantly during the year of 2011. The increase of the growth is contributed by the increase of funding and financing products of Sharia Banks. Risk management and funding and financing products of a bank are things that have a very close relationship in the Sharia banking. Bank Indonesia as central bank also has a special interest in establishing provisions to all banks in Indonesia to be able to manage their risks. Risks posed to Sharia Banks have several types inherited from products or services offerred to their customer. One of them is legal risk. Legal risks may derive from the weaknesses of legal aspects of products or services of Sharia Bank. Therefore, Mudharabah Muqayyadah On Balance Sheet (MMOB) as a product of PT Bank XYZ which has nature of funding as well as financing, poses legal risks originate from the weaknesses of its legal aspects. Legal risk in a transaction may be in the form of incomplete requirements for a valid agreement which may originates from several factors of legal risks. Factors of legal risk of a transaction cover incorrect legal structure, absence of consent of the parties, absence of competence of the parties, no certain objects, no permissible cause, imperfect clauses in the agreement, and incomplete legal documents.This final project is composed to identify the legal risks that may arise from MMOB transaction, its risk priority and the way to mitigate such legal risks. Legal risks of MMOB transaction derived from the weaknesess of legal aspects of MMOB Transaction. Legal risks of MMOB transaction occur in every steps of MMOB process. MMOB process steps consist of Process Step 1 Offering Product to Customer, Process Step 2 Product/Transaction Explanation, Process Step 3 Structure Selection, Process Step 4 Prepare Legal Document, and Process Step 5 Closing Transaction.The assessment of risk priority number (RPN) used Failure Modes and Effect Analysis (FMEA). The assessment result has revealed that the rank of RPN of MMOB Transaction which describe the consecutive rank of RPN is in the Process Step 3 of Structure Selection, Process Step 3 Prepare Legal Document, Process Step 4 Closing Transaction, Process Step 2 Product/Transaction Explanation, and Process Step 1 Offering Product to Customer.The legal risks of MMOB transaction have effects that the agreements can be deemed either void or voidable. Mitigation of legal risk of MMOB transaction is carried out through strengthening legal aspects of MMOB transaction by perfecting legal structure of MMOB transaction, revising legal document related to MMOB transaction, peparing procedures of marketing and offering MMOB transaction and preparing legal risk management policy.Â Keyword : risk management, legal risk, contract law, islamic bank, mudharabah muqayyadahÂ